Neuropsychological and electrophysiological correlates of self- and error-awareness in focal lesion patients and young adults - Hoerold, Doreen (Trinity College (Dublin, Ireland). School of Psychology, 2009)
This thesis examines numerous aspects of deficit awareness, both among nonneurological participants and patients with circumscribed neural injury, in order to increase our understanding of the neuropsychological, neuroanatomical and electrophysiological bases of human self-awareness. Following a review of the extant literature on this topic, three studies are presented which adopt a multi-method approach to assessing self- and error-awareness, including the use of contemporary neuroscience paradigms that can be utilized in novel ways to explore clinically impaired self-awareness.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin.